Estimasi Volume , Biomassa Dan Karbon Hutan Rakyat Jati Unggul Nusantara Desa Dungus Kecamatan Dagangan Kabupaten Madiun - Rohmatiah, Ahadiati; Lukito, Martin (JURNAL AGRI-TEK, 2015)
The purpose of this study is the potential Wood and plant biomass potential Jati Unggul Nusantara (JUN). and carbon content (C) stored in various organs of plants, and the potential of plantations to absorb CO2. The study was conducted on private forest in the village Dungus JUN plants. District. Kec. Dagangan . Kab. Madiun, through activities in the forest inventore age of five measurements of wet weight of leaves and twigs, stems, branches and leaves made with the technique of "destructive sampling". Carbon content measurements performed by the indirect method. Potential CO2 uptake was estimated by mass weight conversion. Estimates of potential standing stock ranged Estimated potential for community forest Teak Dungus in the village district. Kec. Dagangan Kab Madiun at age 5 year. The total volume of 53.173 m3 The content of plant biomass ranged JUN of 196.74 kg, reaching 52.90 % of the average weight of the wet conditions. Total biomass potential stand JUN is 121.1 tons. Or when in the state in unit area/Ha, the average biomass of 27.30 ton/Ha. Potential carbon content in biomass conversion method ranged average of 13.65 ton of CO2/Ha. total potential carbon content stand JUN is 46.61 tons of Carbon. When converted into units of v/ha are ranged from 12.45 to 13.65 tons of CO2/Ha. The composition of the carbon content of each component tree is also different, which is the highest in the stem component, followed by branches, roots, and leaves. The amount of CO2 sequestration potential in the conversion of the plant when the plant amount equivalent to 367.17 tons of CO2 overall JUN. Allometric equation which is derived in this study as follows Relationship between volume JUN with a diameter at breast height (DBH) trees Volume = Y = 0.0002587 DBH (cm) 2312 Relationship Biomass and Carbon content with diameter at breast height (DBH) is a model of power with WT / CT = 0.051 DBH 2231 for biomass and WT / CT = 0.052 DBH 2,231 for carbon content.Keywords: Potential, Biomass;; carbon dioxide, CO2 absorption